Chemical composition of essential oil of the Atalantia guillauminii Swingle (Rutaceae) in Pu Mat national park, Nghe An province - Hung, Nguyen Viet; Thai, Tran Huy; Dung, Nguyen Anh; Dai, Do Ngoc (Academia Journal of Biology, 2016)
The essential oils from three parts of the species Atalantia guillauminii (Rutaceae) collected in Pu Mat National Park have been studied. The essential oils obtained from leaf, stem and fruits of Atalantia guillauminii by the steam distillation was 0.3%; 0.2% and 0.5%, (w/w), respectively. Of the total of 47 components identified in the leaves, the major constituents are β-phellandrene (33.4%), α-phellandrene (10.6%) and o-cymene (5.8%). Similrly, of the thirty two components identified in stem, which take about 96,7% of the total composition of the oil, the major constituents of the essential oil are limonene (24.5%), sabinene (14.6%), bicyclogermacrene (7.6%), bis (2-ethylhexyl) phthalate (7.6%) and β-caryophyllene (6.6%). Of the total of thirty four components, which take about 91.7% of the total composition of the oil, sabinene 36.4%), β-phellandrene (19.5%) and α-phellandrene (8.0%) are identified as the major components. This is the first time, the chemical compositions of the leaf, stem and fruits essential oils of Atalantia guillauminii from Vietnam were being reported.